Kampanye Visual Edukatif untuk Pelestarian Kearifan Lokal dan Pembentukan Karakter Peserta Didik - A ALI; Sayidiman Sayidiman; Muhammad Akil Musi; Hardianto Rahman; Andika Marsuki (GERAKAN EDUKASI DAN MASYARAKAT NUSANTARA, 2025)
This community service activity aims to raise public awareness, especially among the younger generation, about the importance of preserving local wisdom and developing character through educational visual campaigns on social media. The activity was motivated by the declining interest of young people in regional cultural values due to the strong influence of globalization and digital media. The implementation method consisted of several stages: identifying local wisdom values, creating educational visual content (infographics, posters, and short videos), publishing the content on social media platforms such as Instagram and TikTok, and evaluating audience engagement. The results showed that using social media as an educational tool effectively attracted public interest and participation in understanding and appreciating local culture. The high level of audience engagement indicated that visual approaches are effective in delivering moral messages and character values. Through this activity, social media proved to function not only as a means of entertainment but also as a medium for education and cultural preservation. Therefore, the educational visual campaign serves as an innovative form of community service in the digital era, relevant to current developments and supporting the formation of Pancasila Student Profiles who are characterized, cultured, and nationally minded.